1862 Terr. of Wash. Stat. 284, ch. 2, § 30 - (:unkn) unknown (My University, 1862)
Prohibited displaying any pistol, Bowie-knife, or other dangerous weapon to a crowd of two or more persons in a rude, angry, or threatening manner.
Keywords: BRANDISHING